Combining machine translation and automated scoring in international large-scale assessments - Jung, Ji Yoon; Tyack, Lillian; von Davier, Matthias (Large-scale Assessments in Education, 2024)
Artificial intelligence (AI) is rapidly changing communication and technology-driven content creation and is also being used more frequently in education. Despite these advancements, AI-powered automated scoring in international large-scale assessments (ILSAs) remains largely unexplored due to the scoring challenges associated with processing large amounts of multilingual responses. However, due to their low-stakes nature, ILSAs are an ideal ground for innovations and exploring new methodologies.
<AI Smry>: This study highlights that automated scoring integrated with the recent machine translation holds great promise for consistent and resource-efficient scoring in ILSAs and shows comparable performance to human scoring.
Keywords: AI: ChatGPT; Educational Area: Assessment Tools & Processes; Evidence: Gaps in Current Research; Evidence: Improve a process; Location: Asia; Location: Europe; Research Design: Non-experimental design; Research Method: Quantitative; Source: Open Source